An interacting quantum atom study of model SN 2 reactions (X- ···CH3 X, X = F, Cl, Br, and I) - Alkorta, Ibon (Journal of computational chemistry, 2018)
© 2017 The Authors Journal of Computational Chemistry Published by Wiley Periodicals, Inc.